An experimental comparison of PID autotuners. (April 2018) - Berner, Josefin; Soltesz, Kristian; Hägglund, Tore; Åström, Karl Johan
Abstract: In this paper two novel autotuners are compared with two industrially available ones. The aim is to see if the research frontline can improve the industry standard of today. Experiments are made on three laboratory processes with different characteristics. Two lag-dominated processes of which one is a level control problem with fast dynamics, and one a temperature control problem with slow dynamics, as well as one delay-dominated level control process. Both the experiments and the obtained controller performances are evaluated and discussed. The results show that the performance of the state-of-the-art industrial autotuners can be significantly improved. Highlights: A comparison of standard industrial autotuners and the research frontline is made. Evaluations on processes with characteristics relevant to the process industry. Obtained controller performance and the experiment procedure are evaluated. The results show that novel autotuners can improve the industry standard significantly.